2019
DOI: 10.3390/jcm8091435
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes for Upper Lumbar Disc Herniation: Decompression Alone versus Fusion Surgery

Abstract: Upper lumbar herniated intervertebral disc (HIVD), defined as L1-2 and L2-3 levels, presents with a lower incidence and more unfavorable surgical outcomes than lower lumbar levels. There are very few reports onthe appropriate surgical interventions for treating upper lumbar HIVD. This study aimed to evaluate the surgical outcome of decompression alone, when compared with spinal fusion surgery. A retrospective study involving a total of 7592 patients who underwent surgery due to HIVD in our institution was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For patients that fail to respond to conservative treatment, surgical treatment should be carried out. Traditional surgical methods include lumbar microdiscectomy and lumbar discectomy combined with intervertebral fusion ( 11 ). Open surgery for the treatment of upper LDH has a satisfactory clinical effect, but the operation requires extensive traction and dissection of paravertebral soft tissues, which tends to impair the stability of intervertebral joints and ligaments and results in increased surgical trauma ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…For patients that fail to respond to conservative treatment, surgical treatment should be carried out. Traditional surgical methods include lumbar microdiscectomy and lumbar discectomy combined with intervertebral fusion ( 11 ). Open surgery for the treatment of upper LDH has a satisfactory clinical effect, but the operation requires extensive traction and dissection of paravertebral soft tissues, which tends to impair the stability of intervertebral joints and ligaments and results in increased surgical trauma ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Incidental durotomy may result in persistent pain through various mechanisms, including direct injury to the nerves or inflammation [ 33 ]. Inadequate or inaccurate decompression during surgery can lead to the persistence or worsening of pain [ 34 ].…”
Section: Etiology—risk Factorsmentioning
confidence: 99%
“…Some authors have reported upper lumbar discs as T12-L1, L1-L2, L2-L3, and L3-L4 [1], while some other studies have considered them as only L1-L2 and L2-L3 [2]. The spinal canals of upper lumbar discs are narrower than those of the lower ones, which may compromise multiple spinal nerve roots or conus medullaris and lead to complex and variable signs [3]. The traditional treatments for ULDH include open posterior lumbar interbody fusion [4], transforaminal lumbar interbody fusion [5], and posterior decompression [6], and only nucleus pulposus enucleation via intervertebral foramen (or fenestration of laminar space).…”
Section: Introductionmentioning
confidence: 99%